Pectin manufacture from calamansi wastes - Baldivia, Gena M. D.; Cunanan, Eugene M.; Liboro, Rosalie Rhodora G.; Uy, Mildred M. (College of Engineering, 1999)
Product: Powdered pectin -- Plant capacity: 255 kg/per day -- Selling price: Php 750.00/kg -- Total capital investment: Php 109,943,755.00 -- Total product cost: Php 35,526,664.00 -- Gross annual sales: Php 57,375,000.00 -- Net income after tax: Php 9,788,610.00 -- Return on investment: 8.90% -- Payback period: 3.80 years -- Plant location: Antipolo, Rizal